On The Validity Of Exploiting The Basic Concepts Of Arabic Linguistics For The Analysis Of English - Fatiha Khelout; Abderrahmane Hadj Saleh; Kamel Khaldi (Al-Lisaniyyat, 2005)
This paper aims at discussing the possibility of exploiting the basic concepts of Arabic linguistics for the analysis of a language other than Arabic, namely English. For this, we start by presenting briefly the neo-khalilian theory, being the main source from which we have extracted the methodological tools and the principles put forward by the first arab grammarians for the description of Arabic many centuries ago ; then, we review how some linguistic units have been defined through a number of western linguistic theories in comparison to the neo-khalilian model of analysis ; finally, we end by explaining why we are trying to apply the neo-khalilian for the analysis of English.